Semiotic of Symbolic Mode in Interpreting Mythology in English Poetry - Mulyoso Mulyoso (TEFLIN, 1999)
This paper is primary based on the assumption that we need theories of literature in order to interpret the literary texts and explain literature as a unique form of communication. The so-far traditional efforts of treating literary study as an intuitive analysis has contributed to the harsh criticism on the study of literature as merely Ã¢â¬Ëthe reading and understanding of literature. Literature teaching has given too much emphasis on the enjoying and understanding of a literary piece, that is to say that merely by understanding the meaning of the language of a text, its cultural references, one is said to be in a position to respond critically to that text Ã¢â¬â thus there is no need for interpretation beyond that. Therefore, this paper is an attempt to interpret a literary text (mythology in English poetry) beyond its literal level by the use of semiotics of symbolic mode approach which allows the intertextual and intratextual analysis.